TO THE QUESTION ABOUT THE CONCEPT OF A PISTOL FRAME - A. Kokin (Теория и практика судебной экспертизы, 2015)
The article considers different approaches to the forensic ballistic examinations of а pistol frames of some models of modern pistols. The proposed position of the author on this issue based on the analysis of the design of firearms limited destruction – pistol Grand Power T12 calibre 10x28T, as well as existing regulations and technical documents.